LANGUAGE ERROR ANALYSIS ON OFFICIAL LETTERS DESA KALILOKA’S KECAMATAN SIRAMPOG KABUPATEN BREBES (ANALISIS KESALAHAN BERBAHASA PADA SURAT DINAS DESA KALILOKA KECAMATAN SIRAMPOG KABUPATEN BREBES) - Ulfiyani, Ulfiyani; Nurika Irma, Cintya (Universitas PGRI Sumatera Barat, 2019)
The purposes of this research are : (1) to describes the Indonesia language eror forms on official letters; and (2) the determinant factors of language error forms on official letters of Desa Kaliloka’s, Kecamatan Sirampog, Kabupaten Brebes. This research is a qualitative descriptive research. The result of this research are as follows. First, the Indonesian language error forms found on the official letters of Desa Kaliloka’s such as: errors in the field of spellings, morphologies, and syntaxes. Second, the determinant factors of Indonesian language error forms on official letters Desa Kaliloka’s are: a) writing official letters only refers to the village had and sampel letters from the subdistrict; b) the official letter writers more than one person; c) no training about official letter from the local government; and d) ignorance of the existance of KBBI and PUEBI which are the basic guidelines of language.